2020
DOI: 10.1109/tpc.2019.2961010
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences Between Chinese and Western User Instructions: A Content Analysis of User Manuals for Household Appliances

Abstract: Research problem: Cultural differences may be increasingly important in technical communication.Research is needed to investigate differences in document design practices and user preferences. This study examines cultural differences between Chinese and Western manuals for household appliances. Literature review: Earlier studies identified a wide range of possible differences between Chinese and Western documents, but the findings are not consistent and do not provide more generic perspectives on cultural diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…However, the results of the previously mentioned content analysis could not confirm these earlier results: no differences were found between the number of visuals and the extent to which visuals are integrated with the text. The results of this recent study, however, showed that different types of visuals are used in Chinese user instructions than in Western user instructions [10,12]. More cartoon-like figures are used in Chinese manuals and more detailed pictures of how a task should be performed are found in Western manuals.…”
Section: Literature Review: Differences Between Chinese and Western Umentioning
confidence: 81%
See 2 more Smart Citations
“…However, the results of the previously mentioned content analysis could not confirm these earlier results: no differences were found between the number of visuals and the extent to which visuals are integrated with the text. The results of this recent study, however, showed that different types of visuals are used in Chinese user instructions than in Western user instructions [10,12]. More cartoon-like figures are used in Chinese manuals and more detailed pictures of how a task should be performed are found in Western manuals.…”
Section: Literature Review: Differences Between Chinese and Western Umentioning
confidence: 81%
“…They are not always only targeted to end users, but sometimes also to technicians, since another study showed that more technical information is to be found in Chinese manuals [9]. A recent content analysis study in which 50 Chinese user manuals for a variety of household appliances were compared with 50 user manuals from Western origin confirmed these earlier results [10].…”
Section: Literature Review: Differences Between Chinese and Western Umentioning
confidence: 82%
See 1 more Smart Citation
“…Western user documentation differs in many aspects from Eastern Asian user documentation. Results of several content analytic studies (Barnum & Li, 2006; Carroll & Delin, 1998; Q. Li et al, 2020a; Wang & Wang, 2009; Zhu & St.Amant, 2007) have suggested differences in the content of instructions, the use of visuals, and—most dominantly—the structure of instructions.…”
mentioning
confidence: 99%
“…Results of the most comprehensive and most recent content analytic study, which compared Chinese and Western manuals for household products, showed that the structure of Chinese instructions is less rigid than that of Western instructions because structuring elements, such as headings, are less systematically used (Q. Li, et al, 2020a). But other studies show that users of instructions from both cultures are equally well able to use instructions with and those without systematic structuring elements (Q.…”
mentioning
confidence: 99%